Operational analysis of the semi-mechanized harvesting in eucalyptus stands in south Tocantins - Silva, Yunis Guilherme; Araújo Filho, Renisson Neponuceno; de Oliveira Melo Neto, José; Marinho Junior, Josué Luiz; Fiedler, Nilton Cesar; Gonçalves, Saulo Boldrini (MAGISTRA, 2022)
Abstract: This work aimed to operationally analyze the semi-mechanized forest harvesting activity for charcoal production in the forest cultivation in the state of Tocantins. The study was conducted in an experimental area of the farm “Vale Verde”, located in the municipality of Aliança do Tocantins-TO. Was evaluated or semi-mechanized harvesting system composed by crawler tractor, chainsaw, stump truck and farm tractor with attached trailer. The same evaluated in mechanical availability, economical and efficient. The results show that a reduction activity takes longer, consuming 85% of the downed duty cycle, within a work cycle of 74% consumed tracking and delimbing element processing activities and required 46% extraction or item element processing activities. of activity time. All activities selected mechanical availability below 80%. The highest operational efficiency value found was 85% in felling activity and the lowest in activity extraction with 51%. The values selected in this study, serving as a basis for producers in the region, establish the operational planning of semi-mechanized forest harvesting activities. Key words: Curves system, Study of times and movements, Operational efficiency.